2016
DOI: 10.1002/ceat.201500286
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Surface Roughness, Internal Crystal Perfection, and Crystal Growth Rate

Abstract: Potential mechanisms affecting growth rate dispersion (GRD) are investigated. Previous studies have identified surface roughness and internal lattice perfection as key mechanisms which are both evaluated with respect to GRD. Crystal growth of potassium dihydrogen phosphate was studied in two solvent mixtures, water and water‐ethanol. The surface roughness was analyzed by atomic force microscopy and the internal crystal perfection by X‐ray diffraction using a synchrotron source. The crystals grown at higher sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Many substances exhibit wide face, directional, and mass growth rate dispersion under different growth conditions. It is shown that dissolution and refaceting narrow these dispersions. , It can be seen from Figures , , and that for all investigated macroscopic external conditions, a wide range of face growth rates exists after refaceting. These growth rate distributions can be described by a simple normal distribution, as was shown previously .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Many substances exhibit wide face, directional, and mass growth rate dispersion under different growth conditions. It is shown that dissolution and refaceting narrow these dispersions. , It can be seen from Figures , , and that for all investigated macroscopic external conditions, a wide range of face growth rates exists after refaceting. These growth rate distributions can be described by a simple normal distribution, as was shown previously .…”
Section: Discussionmentioning
confidence: 91%
“…Crystal growth rate dispersion, which occurs for many substances, , complicates analysis of ( R , σ) dependence. Dispersion of growth rates in one direction (sum of growth rates of opposite faces) is wider than dispersion of face growth rates.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, there was a decrease in the average lattice strain in CR4 and CR5, which showed similar average lattice strain values as that of CR1 (0.041). Since the lattice strain is inversely related to the crystal perfectness, low average lattice strain values indicated that the fat crystal network of CR4 and CR5 was highly ordered [ 59 ]. In a nutshell, we observed that the inclusion of GO in the oleogels enhanced the compactness and formation of large-sized crystallites with very low lattice imperfections.…”
Section: Resultsmentioning
confidence: 99%
“…These morphologic characteristics of fayalite and their absence at the surface of FeO-rich olivine crystals identified in chondrites could indicate a change in the chemical composition of the fluid. Previous studies show that crystals growing in high supersaturation solutions have rougher, irregular surfaces (on a macroscopic rather than molecular scale) than those growing in low supersaturation solutions (Galbraith et al, 2016;Pantaraks et al, 2007). Although the difference in saturation for the chemical composition of the fluid in chondrites and the hydrothermal experiment cannot be disregarded, these morphologic characteristics could have been erased by subsequent metamorphic processes in chondrites (Allende, Kaba, and Tieschitz; Brearley, 2009;Dobric a & Brearley, 2014;Krot et al, 1997;Watt et al, 2006;Weisberg et al, 1997).…”
Section: Discussionmentioning
confidence: 98%